TRPV1 Channels in the Central Nervous System as Drug Targets - Loris A. Chahl (MDPI AG, 2024)
TRPV1 channels are polymodal cation channels located predominantly on primary afferent neurons that are activated by inflammatory mediators, capsaicin (the active component in chili peppers), and noxious heat. TRPV1 channel antagonists are potential new analgesic agents, but their development has been hindered by the finding that they also produce loss of thermal homeostasis and response to noxious heat. Results from recent studies of the TRPV1 channel indicate that it might be possible to develop TRPV1 channel antagonists that inhibit pain without affecting noxious heat sensation. TRPV1 channels are also present in the central nervous system (CNS) and have been implicated in learning, memory, and behaviour. TRPV1 channel modulators have been proposed to have possible therapeutic potential in the treatment of neurological and psychiatric conditions. However, further understanding of the role of TRPV1 channels in the CNS is required before therapeutic advances in the treatment of neuropsychiatric conditions with TRPV1 channel modulators can be made.